The Use of Long-Term Indomethacin Stabilizes Cervical Length in Twin Pregnancies [7Q]. (May 2017) - Shannon, Allison; Crimmins, Sarah; Hanna, David; Kopelman, Jerome; Harman, Chris; Turan, Ozhan
Abstract : INTRODUCTION: To determine if the use of early onset (less than 25 weeks) long-term indomethacin therapy (greater than 48 hours) (LIT) stabilizes the cervical length (CL) in dichorionic-diamniotic twin gestations (DCDA-T) that are complicated by a short cervix. METHODS: DCDA-T pregnancies with short CL (less than 30 mm) after 18 weeks were identified. Serial CL measurements, other treatments (17 OH-P, vaginal progesterone) and outcomes were collected. Patients with cervical cerclage were excluded. The degree of cervical shortening from initial to last examination was compared in patients with a short CL and women with a normal CL at same gestational age (GA). Longitudinal analysis of the change in CL was modeled using mixed-model regression analysis and predicted values were compared using comparisons of the slope analysis. RESULTS: Out of 77 patients, 32 (42%) received LIT. The GA at initial ultrasound was similar between groups (P=0.6). Initial and last CLs were shorter in LIT group (21 mm vs 43 mm and 11.5 mm vs 36 mm) (P < .0001 for both). A total of 434 (LIT=191, Normal CL=243) longitudinal CL examinations were used for mixed-model regression analysis. CL improved or did not change in LIT group (0-0.4 mm/week) (CL= 0.0353GA2-1.5458GA+32.399, R 2 =0.06). However, in normal CL group, CL was declined by 0.8-1.9 mm/w (CL=0.0529GA2-4.1356x+105.25) (P < .00001). There were no reportable antenatal side effects. CONCLUSION: Early onset long-term indomethacin therapy in DCDA-T with a short cervix provides an alternative treatment modality to stabilize cervix.